Keterampilan Mahasiswa dalam Membuat Produk Olahan Berbahan Dasar Buah Kelapa - Latipah, Nurlia; Syarifuddin, Syarifuddin (IJIS Edu : Indonesian Journal of Integrated Science Education, 2019)
Penelitian ini bertujuan untuk mengetahui keterampilan Mahasiswa semester 5 Tadris IPA IAIN Bengkulu Tahun Akademik 2018/2019 dalam membuat produk olahan berupa minyak  dengan bahan dasar buah kelapa. Penelitian ini dilakukan dengan memberikan tugas kepada mahasiswa untuk membuat minyak dari bahan dasar buah kelapa dengan menggunakan metode yang telah dikembangkan sebelumnya . Mahasiswa juga diwajibkan membuat laporan hasil kegiatan dalam pembuatan minyak serta mengumpulkan minyak yang telah dihasilkan. Hasil penelitian menunjukkan seluruh mahasiswa yang menjadi sample pada penelitian ini berhasil membuat minyak dengan bahan dasar buah kelapa. Hasil penelitian juga menunjukkan bahwa seluruh sample pada penelitian ini membuat minyak dengan cara yang berbeda-berbeda sehingga dihasilkan produk minyak dengan jenis dan kegunaan yang berbeda. Hal ini menunjukkan bahwa Mahasiswa tadris IPA IAIN Bengkulu pada penelitian ini memiliki kreatifitas yang cukup tinggi dalam menghasilkan produk. This study aims to determine the skills of the 5th semester students of Tadris IPA IAIN Bengkulu Academic Year 2018/2019 in making processed products in the form of oil based on coconut. This research was carried out by giving students the task of making oil from coconut fruit base materials using a method that had been developed previously. Students are also required to make a report on the results of activities in making oil and collecting oil that has been produced. The results of the study showed that all students who were the samples in this study succeeded in making oil with the basic ingredients of coconut. The results also showed that all samples in this study made oil in different ways so that oil products with different types and uses were produced. This shows that Student Of Tadris IPA of  IAIN Bengkulu  in this study have quite high creativity in product something.This study aims to determine the skills of the 5th semester students of Tadris IPA IAIN Bengkulu Academic Year 2018/2019 in making processed products in the form of oil based on coconut. This research was carried out by giving students the task of making oil from coconut fruit base materials using a method that had been developed previously. Students are also required to make a report on the results of activities in making oil and collecting oil that has been produced. The results of the study showed that all students who were the samples in this study succeeded in making oil with the basic ingredients of coconut. The results also showed that all samples in this study made oil in different ways so that oil products with different types and uses were produced. This shows that Student Of Tadris IPA of  IAIN Bengkulu  in this study have quite high creativity in product something.